Does Environmental Policy Promote Energy Efficiency? Evidence From China in the Context of Developing Green Finance - Peng, Jiaying; Zheng, Yuhang (Frontiers in Environmental Science, 2021)
In response to the dilemma between economic development and environmental protection, green finance is an effective tool for environmental regulation. Based on the stochastic frontier analysis method to measure the annual energy efficiency of China’s provinces from 2001 to 2017, the promotion effect of green finance on energy efficiency and the intermediary effect of green technology innovation are tested and analyzed in our study. The results show that green finance can significantly improve energy efficiency. Specifically, green finance makes stronger effect on energy efficiency in provinces with rich resource endowments, high levels of economic development, and high degree of marketization. Green finance can improve energy efficiency through the development of new energy technologies and disruptive green innovation, which provides important supports for formulating policies to optimize energy structure and improve energy efficiency.